2013
DOI: 10.1016/j.str.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Dimensional Structure of the Biotin Carboxylase-Biotin Carboxyl Carrier Protein Complex of E. coli Acetyl-CoA Carboxylase

Abstract: SUMMARY Acetyl-coenzyme A (acetyl-CoA) carboxylase is a biotin-dependent, multifunctional enzyme that catalyzes the regulated step in fatty acid synthesis. The Escherichia coli enzyme is composed of a homodimeric biotin carboxylase (BC), biotinylated biotin carboxyl carrier protein (BCCP), and an α2β2 heterotetrameric carboxyltransferase. This enzyme complex catalyzes two half-reactions to form malonylcoenzyme A. BC and BCCP participate in the first half-reaction, whereas carboxyltransferase and BCCP are invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…The structural organization of fatty acid synthases and polyketide synthases also support this supposition (Smith and Sherman, 2008;Chan and Vogel, 2010;Bukhari et al, 2014). Structural characterization of these enzymes indicate catalytic coordination is facilitated by the quaternary organization of the catalytic subsites, which have to be iteratively visited by intermediates of the overall reaction (Broussard et al, 2013;Tran et al, 2015;Wei and Tong, 2015;Hunkeler et al, 2016).…”
Section: Discussionmentioning
confidence: 71%
“…The structural organization of fatty acid synthases and polyketide synthases also support this supposition (Smith and Sherman, 2008;Chan and Vogel, 2010;Bukhari et al, 2014). Structural characterization of these enzymes indicate catalytic coordination is facilitated by the quaternary organization of the catalytic subsites, which have to be iteratively visited by intermediates of the overall reaction (Broussard et al, 2013;Tran et al, 2015;Wei and Tong, 2015;Hunkeler et al, 2016).…”
Section: Discussionmentioning
confidence: 71%
“…The structure of the E. coli BC‐BCCP was solved recently, the BCCP thumb is solvent exposed within the BC‐BCCP complex (Broussard et al ., ). Strikingly, we were not able to detect interaction between native E. coli GlnK and the His‐BC:holo‐BCCP complex mobilized on a Ni 2+ magnetic resin, suggesting that holo‐BCCP cannot interact with GlnK and BC simultaneously.…”
Section: Discussionmentioning
confidence: 97%
“…However, given the similarity of BADC and BCCP with respect to primary amino acid sequence ( Figure 5A), predicted structure ( Figure 5B), and dimerization capability (Figure 4), the parsimonious interpretation of these data is that BADC proteins inhibit hetACCase activity by competing with BCCP for binding to other hetACCase subunits. The crystal structure of the E. coli BC/BCCP subcomplex consists of two dimers of BC held together by four BCCPs, thus having a BCCP:BC ratio of 1:1 (Broussard et al, 2013). In contrast, proteomics (Ishihama et al, 2008), in vivo labeling (Choi-Rhee and Cronan, 2003), and ribosome profiling studies (Li et al, 2014) have observed a BCCP:BC ratio of 2:1.…”
Section: Discussionmentioning
confidence: 99%
“…Each lane was separated into 0.5-cm segments and subsequently diced into ;1-mm 3 gel Schematic illustrating the proposed mechanism of BADC inhibition. The BC/ BCCP subcomplex design was made based on the crystal structure in E. coli (Broussard et al, 2013), consisting of two dimers of BC and four BCCP proteins. The BADC proteins compete with BCCP for binding to BC.…”
Section: Mass Spectrometry Sample Preparation and Analysismentioning
confidence: 99%